Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Sari Melati Kencana Cabang RC Veteran Jakarta Selatan - Lestari , Dewi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to determine the effect of work motivation and work discipline on employee performance at PT. Sarimelati Kencana, South Jakarta Veterans RC Branch, either partially or simultaneously. The method used is quantitative. The sampling technique used is saturated sampling and the sample obtained in this study amounted to 58 respondents. Data analysis used validity test, reliability test, classical assumption test, and regression analysis. The results showed that work motivation had a significant effect on employee performance. Work discipline had a significant effect on employee performance. Work motivation and work discipline have a significant effect on employee performance at PT. Sarimelati Kencana RC Veterans South Jakarta Branch